Vitamin D deficiency and Parathormone levels in Punjabi Pakistani Population - Shafiq, Hamid; Majeed, Asifa (Pakistan Journal of Physiology, 2019)
Background: Vitamins are organic compounds that play significant role in management of metabolic processes. Vitamin D is considered a nutrient associated with a bio-signaling action. It has vital participation in constant maintenance of calcium level in both intra and extracellular body fluids. Objective: The present study analyzed the vitamin D and PTH levels in Punjabi population of Pakistan. Methods: Sample collection was done from October 2017 to October 2018 from various local health institutes of Punjab and blood samples of four hundred subjects were collected. The quantitative measurement of vitamin D was obtained by automated competitive chemiluminescence immunoassay method. PTH levels were calculated by direct Chemiluminescence using Acridinium Ester technology method. The values of vitamin D thus obtained were compared with levels of parathyroid hormones along within different age groups. Results: Overall 77.5% of studied population was deficient/insufficient of vitamin D. The 35% individuals in age group up to 20years were deficient/insufficient while 88.8% were in second group aged up to 40years. The 95.8% people showed deficiency/insufficiency third group aged up to 60 years. On comparison of vitamin D with parathyroid hormone levels; a significant negative association was observed and vice versa. Our study is in agreement with others that demonstrate a high prevalence of cholecalciferol deficiency in many populations. Conclusion: We conclude that measurement of Vitamin D is of paramount importance in our population so that timely correction of its deficiency can ward off many complications resulting from its direct and indirect (through raised parathyroid hormone) effects.